Integration of Fertilizer Nitrogen, Farmyard Manure and Multi-strain Microorganisms for Sustainable Production of Rice-Wheat System - Bijay-Singh; Yadvinder-Singh, H.S. Thind, Sandeep Sharma, Varinderpal-Singh, H.S. Sran (Journal of the Indian Society of Soil Science, 2016)
Use of high rates of commercial nitrogen (N) fertilizers over the years has resulted in adverse effects on soil and environment health. Integrated use of fertilizer N and organic N sources is expected to reduce the N losses and improve N use efficiency. The present field experiment was conducted for two years to evaluate the effects of commercially available multi-strain inoculant ‘Fertimine’ and farmyard manure (FYM) applied at variable rates of fertilizer N on the nutrition of rice-wheat system. Four treatment combinations of FYM (15 t ha-1, fresh weight) and fertimine were applied to main-plots and four N levels to sub-plots in factorial split-plot design. In the absence of fertimine and FYM, significant increase in rice yield was observed up to 120 kg N ha-1 during first season and 80 kg N ha-1 during second season. The application of FYM and fertimine significantly increased mean grain yield of rice by 12 and 5 per cent over no FYM and fertimine, respectively. Significant interaction effect of fertimine and fertilizer N observed on rice grain yield suggested that fertimine significantly increased the rice yield at low rates of fertilizer N. While fertilizer N and FYM caused significant increase in the total uptake of N, P and K in rice, fertimine showed significant increase in total P uptake only. The FYM applied to rice showed significant residual effect on the yield and total N, P and K uptake in the subsequent wheat. Application of FYM significantly improved the soil chemical and biological properties after two cycles of rice-wheat rotation.